2017
DOI: 10.1152/ajpheart.00752.2016
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of mitochondrial proteins by GCN5L1 promotes enhanced fatty acid oxidation in the heart

Abstract: Lysine acetylation is a reversible posttranslational modification and is particularly important in the regulation of mitochondrial metabolic enzymes. Acetylation uses acetyl-CoA derived from fuel metabolism as a cofactor, thereby linking nutrition to metabolic activity. In the present study, we investigated how mitochondrial acetylation status in the heart is controlled by food intake and how these changes affect mitochondrial metabolism. We found that there was a significant increase in cardiac mitochondrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
96
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(103 citation statements)
references
References 40 publications
7
96
0
Order By: Relevance
“…Furthermore, we and others have shown that mitochondrial protein acetylation is significantly increased in various tissues during obesity [13][14][15][16]. Specifically in the heart, we have shown that an increase in acetylation results in increased activity of several FAO enzymes, which is regulated in part by the mitochondrial acetyltransferase GCN5L1 [16]. These findings place nutritional inputs, lysine acetylation, substrate utilization, and GCN5L1 at a key regulatory node in cardiac energy metabolism.…”
Section: Introductionsupporting
confidence: 58%
See 4 more Smart Citations
“…Furthermore, we and others have shown that mitochondrial protein acetylation is significantly increased in various tissues during obesity [13][14][15][16]. Specifically in the heart, we have shown that an increase in acetylation results in increased activity of several FAO enzymes, which is regulated in part by the mitochondrial acetyltransferase GCN5L1 [16]. These findings place nutritional inputs, lysine acetylation, substrate utilization, and GCN5L1 at a key regulatory node in cardiac energy metabolism.…”
Section: Introductionsupporting
confidence: 58%
“…Pougovkina et al demonstrated that circulating free fatty acids, prevalent in obesity and diabetes, are the main source of acetyl-coA used for lysine acetylation [12]. Furthermore, we and others have shown that mitochondrial protein acetylation is significantly increased in various tissues during obesity [13][14][15][16]. Specifically in the heart, we have shown that an increase in acetylation results in increased activity of several FAO enzymes, which is regulated in part by the mitochondrial acetyltransferase GCN5L1 [16].…”
Section: Introductionsupporting
confidence: 51%
See 3 more Smart Citations